2015
DOI: 10.1186/s12947-016-0079-y
|View full text |Cite
|
Sign up to set email alerts
|

Rotational method simplifies 3-dimensional measurement of left atrial appendage dimensions during transesophageal echocardiography

Abstract: BackgroundNot all echo laboratories have the capability of measuring direct online 3D images, but do have the capability of turning 3D images into 2D ones “online” for bedside measurements. Thus, we hypothesized that a simple and rapid rotation of the sagittal view (green box, x-plane) that shows all needed left atrial appendage (LAA) number of lobes, orifice area, maximal and minimal diameters and depth parameters on the 3D transesophageal echocardiography (3DTEE) image and LAA measurements after turning the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…In addition, 3D-TEE has been shown to be superior to 2D-TEE for various types of LAA orifice shapes. Recently, research has shown that the perimeter-derived circumferential orifice diameter had the best performance in occlusion sizing among three 3D-TEE parameters ( 22 ). Consistently, our study found that the novel 3D-TEE measurement was superior in LAA clipping via VATS compared with the 2D-TEE or VATS direct measurements.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, 3D-TEE has been shown to be superior to 2D-TEE for various types of LAA orifice shapes. Recently, research has shown that the perimeter-derived circumferential orifice diameter had the best performance in occlusion sizing among three 3D-TEE parameters ( 22 ). Consistently, our study found that the novel 3D-TEE measurement was superior in LAA clipping via VATS compared with the 2D-TEE or VATS direct measurements.…”
Section: Discussionmentioning
confidence: 99%
“…Three-dimensional TEE can be used to quickly obtain a perpendicular LAA section, and the multisection surface can display the diameter of the LAA opening in real time, reduce the steps required during surgery, and shorten the measurement time. It can directly image the complex anatomical structure of the LAA and display its shape, internal structure, and thrombus [19] in 3D images. Therefore, it plays an important role in screening patients, selecting a suitable plugging device, and ensuring the sealing effect.…”
Section: Discussionmentioning
confidence: 99%
“…Yosefy et al advocated that rotational 3DTEE method had the similar accuracy as those of RT3DTEE (measured directly from the original 3D views) and CT in assessing LAA. The aim of this study was to investigate whether or not online RT3DTEE methods can provide the same information of LAA as that of off‐line.…”
Section: Introductionmentioning
confidence: 99%